Pengaruh Kepemimpinan Dan Motivasi Kerja Islami Terhadap Kinerja Karyawan Pada Depot Rawon Rosobo Mojoagung - Ansori, Fitrian; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2019)
This study aims to examine the influence of leadership and motivation of Islamic work on employee performance at Depot Rawon Rosobo Mojoagung. This research was conducted using an associative quantitative approach. The samples used in the study were all employees at the Depot Rawon Rosobo Mojoagung, amounting to 37 people. This study used a questionnaire that was measured using a Likert scale and analyzed using SPSS version 23. The results of this study indicate that partially Islamic leadership variables (X1) do not significantly influence employee performance variables (Y). The motivation variable of Islamic work partially influences significantly on employee performance variables (Y). Simultaneously Islamic leadership variables (X1) and Islamic Work Motivation (X2) have a significant influence on employee performance variables (Y).